Aubrey Aronson: capstone - Aronson, Aubrey, artist (Colorado State University. Libraries, 2015)
The artist's statement: My work is about the blending of Illustration and Graphic Design. Often times Graphic Design is seen as an inferior art form. However, some of the best design qualities I have ever seen were in fine art, and some of the greatest fine art I have seen were in design pieces. I want to break down the walls between illustration and design to show how beneficial they are together. There is so much more control when you produce the "art" and the "design". While I believe they each have their own unique qualities and are separate entities, one is not more artistic than the other, and I hope to show that through my work.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.